Influence of pecan nut pretreatment on the physical quality of oil bodies - Zhang, Pujuang; Di Bari, Vicenzo; Briars, Rhianna; Taher, Zarani Mat; Yuan, Jiamiao; Liu, Guangqin; Gray, David A. (Hindawi, 2017)
A supply of pure, intact oil bodies is essential for carrying out morphological and biochemical studies of these plant organelles, and exploring their application. Preparation requires a carefully controlled breakage of plant cells, followed by separation of the oil bodies from cytoplasm and cell debris. This paper focuses on the recovery and characterisation of oil bodies from pecan nuts where no work has been published to date. The results showed that soaking softens the nut tissue, and appears to reduce the damage to oil bodies during grinding and centrifugal force must be carefully selected to minimise oil bodies damage on recovery. A 24h soaking time coupled with a 5500 RCF recovery force allows for the recovery of intact pecan nut oil bodies.